Genomic and precision medicine foundations, translation, and implementation - Ginsburg, Geoffrey S.; Willard, Huntington F. (Elsevier/AP, 2017)
Genomic and Precision Medicine: Cardiovascular Disease, Third Edition, focuses on the applications of genome discovery on the broad spectrum of cardiovascular disorders. Each chapter is organized for the application of genomics and personalized medicine tools and technologies to a) Risk Assessment and Susceptibility, b) Diagnosis and Prognosis, c) Pharmacogenomics and Precision Therapeutics, and d) Emerging and Future Opportunities in the field.--Provided by publisher.